The role of Managing Knowledge Flows in Improving The Quality of Supervisory Work According to ISSAI 40 Quality Control Standard: A Survey Study - Mutlag, Waleed Saiwan; Hussain, Khansaa Naser; Abdulahad, Alaa Fareed (CENTRAL ASIA AND THE CAUCASUS, 2022)
The research seeks to identify the role of knowledge flow management in improving the quality of external auditing as well as the extent of awareness of the importance of managing knowledge flows in the work of external audit teams by focusing on knowledge flow processes (knowledge mobilization, knowledge diagnosis, knowledge generation, knowledge acquisition, knowledge sharing, and knowledge implementation). The questionnaire was used to collect information to prove the research hypothesis. It was distributed to a sample of (80) employees of the Federation Board Supreme Audit (FBSA) and analyzed using the (SPSS V.26) program. The quality of supervisory work in accordance with the International Organization for Supreme Audit Institutions (INTOSAI) Quality Control Standard (ISSAI 40) through its contribution to improving the scientific efficiency of FBSA employees, improving practical practices, increasing expertise, and enhancing auditors' ethical behavior.